2015
DOI: 10.1121/1.4922175
|View full text |Cite
|
Sign up to set email alerts
|

Viscous torque on spherical micro particles in two orthogonal acoustic standing wave fields

Abstract: This paper reports the experimental results of the acoustic rotation of spherical micro particles because of two orthogonal standing waves. When the standing waves are excited at equal frequency but with a phase shift between two external voltage signals there is an acoustic streaming around the particles. This streaming is due to a time averaging of the acoustic wave field and produces a nonzero viscous torque on the particles, driving them to rotate. The work investigates the micro-particle rotation due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 20 publications
3
45
2
Order By: Relevance
“…Therefore, measuring their value for our spheres could largely improve the torque balance. Importantly, the fact that absorption within the sphere is the dominating driving mechanism contrasts with previous results restricting the description to the viscous boundary layer around the sphere [23,25] or neglecting absorption processes entirely [33]. Finally, within the particle size range considered theoretically, the large contribution of the quadrupolar oscillation mode, even for a/λ < 0.05 (see the close view in Fig.2c), is in contradiction with the common assumption that it can be neglected in the long wavelength (Rayleigh) scattering regime (a/λ 1).…”
contrasting
confidence: 76%
See 1 more Smart Citation
“…Therefore, measuring their value for our spheres could largely improve the torque balance. Importantly, the fact that absorption within the sphere is the dominating driving mechanism contrasts with previous results restricting the description to the viscous boundary layer around the sphere [23,25] or neglecting absorption processes entirely [33]. Finally, within the particle size range considered theoretically, the large contribution of the quadrupolar oscillation mode, even for a/λ < 0.05 (see the close view in Fig.2c), is in contradiction with the common assumption that it can be neglected in the long wavelength (Rayleigh) scattering regime (a/λ 1).…”
contrasting
confidence: 76%
“…The angular speed Ω = 2π × f r 70 rad/s suggests that the driving acoustic torque Γ on the spheres is balanced by the drag Γ D = −8πµa 3 Ω −10 pN.m acting in the opposite direction in a fluid of density ρ = 1000 kg/m 3 and viscosity µ = 1mP a · s for which the low Reynolds number approximation Re= a 2 Ω/ν 1 holds. Note that inertial effects acting in a time scale of a few milliseconds [23] are unresolved with this setup.…”
mentioning
confidence: 99%
“…In addition, it is shown that the high frequency used in the experiment (above 35 MHz) allows tenths of micron size particles to be simultaneously put in motion in the same minute volume. These characteristics open new perspectives for labs on chips since torques used up to now to manipulate objects were obtained under action of bulk acoustic waves (BAW) 18 or evanescent waves 19 in the MHz range. Compared to optical tweezers, the transfer of momentum from acoustic streaming is an additional tool to generate torques for particles of various compositions and shapes and which have no equivalent in optics.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous rotation of tile, syringe and other axisymmetric objects has been realized using acoustic vortex beam that is generated by thermoacoustic or individually addressed transducers [28][29][30][31][32]. Another way to rotate the micro-particle is employing the viscous torque resulted from the acoustic streaming in the viscous boundary layer around the particle [33][34][35]. The above-mentioned two methods are applicable to continuous rotation, especially spherical object, but are unable to stop at certain angular position [27,28,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Another way to rotate the micro-particle is employing the viscous torque resulted from the acoustic streaming in the viscous boundary layer around the particle [33][34][35]. The above-mentioned two methods are applicable to continuous rotation, especially spherical object, but are unable to stop at certain angular position [27,28,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%